PENCIPTAAN BUKU ILUSTRASI TENTANG TARI REMO SEBAGAI UPAYA PENGENALAN KEPADA ANAK-ANAK - Magdalena, Helen Dwi; Fianto, Achmad Yanu Alif; Hidayat, Wahyu (Jurnal Art Nouveau, 2015)
Abstract: Remo dance is one of the traditional dance form of East Java that is expressed from the vibrations of the soul and emotion society of East Java. Dance movements Remo retrieved from the vibrations of the soul and emotions of the people of East Java. Remo dance as a form of expression that values life more assertive attitude appeared, hard, fast and attentive staff that remain in the control. The adapt model soldiering dance form for the hopes and longings of the community over the values of heroism. Heroism is a melee of cultural dance creations with Remo directly through the construction of the military institution ludruk. Remo dance currently almost marginalized and replaced with modern dance. It takes a design media information in the form of book illustration to lift such cultural values, philosophy of meaning contained in the dance movements Remo as a preservation of cultural values. The creation of this book done by the approach of observation, interviews and existing studies using the viewpoint of keyword results of literature review, namely, children, dance Remo, culture and book illustration. By using descriptive analysis methods-qualitative indicators supported by STP and USP are obtained by